2021
DOI: 10.3390/nano11082123
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Kinetics and Reaction Mechanism for Photodegradation Tetracycline Antibiotics over Sulfur-Doped Bi2WO6-x/ZnIn2S4 Direct Z-Scheme Heterojunction

Abstract: The rational design of direct Z-scheme heterostructural photocatalysts using solar energy is promising for energy conversion and environmental remediation, which depends on the precise regulation of redox active sites, rapid spatial separation and transport of photoexcited charge and a broad visible light response. The Bi2WO6 materials have been paid more and more attention because of their unique photochemical properties. In this study, S2− doped Bi2WO6-x coupled with twin crystal ZnIn2S4 nanosheets (Sov−BWO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The EPR spectra show that no signal is detected under the dark condition ( Figure 6 a). In contrast, strong signals with a peak intensity of 1:2:2:1, which belong to the OH radicals, are detected when Cu x O/MOF is irradiated with the visible light for 1–10 min [ 55 ]. Additionally, the DMPO-O 2 − signals in the methanol solution are shown in Figure 6 b.…”
Section: Resultsmentioning
confidence: 99%
“…The EPR spectra show that no signal is detected under the dark condition ( Figure 6 a). In contrast, strong signals with a peak intensity of 1:2:2:1, which belong to the OH radicals, are detected when Cu x O/MOF is irradiated with the visible light for 1–10 min [ 55 ]. Additionally, the DMPO-O 2 − signals in the methanol solution are shown in Figure 6 b.…”
Section: Resultsmentioning
confidence: 99%
“…The negative slopes indicated that the semiconductors are n-type and it was further employed to determine band edge positions of the semiconductors to compare with radical experiments to substantiate the interfacial charge transfer to follow indirect Z-scheme with Bi as the electron mediator between BiOCl and Bi 2 O 3 . There are numerous photodegradation experiments that have been conducted with different photocatalytic Z-scheme heterojunctions towards degradation of single [10] , [78] , [79] and multiple [80] tetracycline antibiotics in water. Dual direct Z-scheme MoS 2 /g-C 3 N 4 /Bi 24 O 31 Cl 10 ternary heterojunction was evaluated towards degradation of TC with 97.5% degradation efficiency in 50 minutes of visible-light irradiation by Kang and co-workers [62] .…”
Section: Z-scheme Photocatalysismentioning
confidence: 99%
“…Diverse tactics investigated for possible improvement of the general efficiency of semiconductors for removal of pharmaceuticals include metal doping [9] , non-metal doping [10] , multi-elemental doping with metals and/or non-metals [11] , use of supports [12] , and formation of heterojunctions [13] , [14] . The contribution of heterojunctions towards abatement of different classes of pharmaceuticals such as β- blockers, hormones, antibiotics, cholesterol-lowering drugs, oestrogens, anti-psychotics, non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics has been studied recently [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Tetracycline hydrochloride (TC) is one of the most common pharmaceutical residues, which is in wide usage on a global scale [ 5 ]. Therefore, a variety of methods have been developed to remove TC from an aqueous environment, including membrane separation, biodegradation, adsorption, Fenton oxidation, and photocatalyst degradation [ 6 , 7 , 8 , 9 , 10 ]. Among them, the photodegradation process is considered as a superior strategy for elimination of TC based on its low cost, sustainable technology, and high removal efficiency [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%